2020
DOI: 10.1371/journal.pone.0231162
|View full text |Cite
|
Sign up to set email alerts
|

A genetically unique Chinese cattle population shows evidence of common ancestry with wild species when analysed with a reduced ascertainment bias SNP panel

Abstract: In Hong Kong, there is a cattle population of~1,200 individuals of uncertain origin and genetic diversity. This population shows heterogeneous morphology, both in body type and pigmentation. Once used as draught animals by the local farmers, they were abandoned around the 1970s due to changes in the economy, and since then have lived as feral populations. To explore the origins of these cattle, we analysed~50k genotype data of 21 Hong Kong feral cattle, along with data from 703 individuals of 36 cattle populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The results point to the fact that the Limousine was involved in the formation of Blonde d'Aquitaine and have common historical ancestors. As expected, the Angus and Red Angus are more genetically linked together and appeared on the same branch as the Hereford breed similarly as reported by Barbato et al (2020). The Charolais breed is separated from other breeds under consideration.…”
Section: Resultssupporting
confidence: 85%
“…The results point to the fact that the Limousine was involved in the formation of Blonde d'Aquitaine and have common historical ancestors. As expected, the Angus and Red Angus are more genetically linked together and appeared on the same branch as the Hereford breed similarly as reported by Barbato et al (2020). The Charolais breed is separated from other breeds under consideration.…”
Section: Resultssupporting
confidence: 85%
“…in [ 29 ] the observed heterozygosities for indicine breeds were lower than 0.21 and those for taurine breeds were higher than 0.3. However, a deeper analysis detected an ascertainment bias that explained this difference since the SNP array chips were predominantly based on taurine breeds [ 30 , 33 , 34 ]. A number of later studies (including the 1000 bull genomes project) based on whole-genome sequencing data showed that indicine breeds had an almost two-fold higher nucleotide diversity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Hong Kong cattle show heterogeneous morphology, both in body type, size and coat colour. A recent analysis of the genotype showed that Hong Kong feral cattle have relatively high levels of genetic distinctiveness and stressed the conservation value of this population [ 36 ]. In this context, GonaCon could be used to increase time between births, with most cattle contributing to the population’s gene pool.…”
Section: Discussionmentioning
confidence: 99%